Metternich, the Slavs and the Habsburg Monarchy, 1842–1849: On the Relationship between Nation and State - Siemann, Wolfram (Historical Studies on Central Europe, 2025)
The prevailing scholarly consensus regarding Prince Metternich’s policy within the framework of the Vienna System of 1815 is that it was hostile and repressive towards the nationalities within the Habsburg Monarchy. However, a re-evaluation of this judgement is provided by the history and circumstances of the Prague Slav Congress of June 1848, as it was here that discussions on the problem of the relationship between national emancipation and state organisation reached a peak. The article examines the knowledge Metternich had of the national diversity of the Slavs even before 1848, and the extent he judged the so-called ‘Pan-Slavism’ not as a problem of nationalities, but as an ideological pretext for Russian expansion. The article also deals with Metternich’s criticism of the repressive Hungarian Slav policy, showing him to be a defender of multinational statehood in Central Europe. In the context of the Frankfurt National Assembly of 1848/49, which sought to delineate the national territory of a unified Germany by the Central European borders of the German Confederation, Metternich recognised the belligerent potential of modern nationalism. His concerns stemmed from his perception of the modern movement to align nationality and state boundaries with language-defined national identities as a perpetual catalyst for state-building conflicts. However, the Emperor’s resistance and the internal bureaucracy’s opposition (the Kolowrat system) hindered the implementation of the model of a multinational federal state he drafted in 1816. This concept bore a resemblance to the notion of ‘Austroslavism’, a concept developed by the Czech historian and politician František Palacký.